Breed- and line-dependent severity of inflammation and necrosis syndrome in AI Boars, and the related risk of inflammation and necrosis in their progeny - Becker, Sabrina; Kochendoerfer, Eva; Kuehling, Josef; Gerhards, Katharina; Lechner, Mirjam; Zinner, Silvia; Lautner, Matthias; Reiner, Gerald; Justus Liebig University Giessen (My University, 2025)
Animal-based measures, such as detecting inflammation in Areas like the tail, ears, teats, coronary band, heels and claws (Swine Inflammation and Necrosis Syndrome, SINS), are used to monitor animal health and welfare. When parameters deviate from the established range, these measures enable prompt action to adjust husbandry practices, feeding regimens and management strategies. In addition to environmental factors, genetics have been shown to play a key role in inflammation and necrosis processes, and selection can reduce the severity of the disease. This study examined whether different breeds of AI boar exhibit different signs of SINS and how these signs are associated with SINS in their Offspring when they are suckling piglets and weaners. Initially, 286 AI boars of 7 breeds from a German artificial insemination center were evaluated for SINS. The following Parameters were assessed: tail base, tail tip, ears, skin, scrotum, coronary bands, heels and claws. Subsequently, 23 Pietrain and Duroc boars were used in combination with a Topigs DL sow line. The progeny of the AI boars was evaluated as suckling and weaned piglets, with the assessment framework encompassing SINS traits. The results revealed significant differences between the breeds and lines, as well as a strong correlation between the SINS phenotypes of the AI boars and the SINS scores of their offspring. The offspring of the 25% most extreme boars exhibited a 17% variation in SINS scores. This association was particularly evident when comparing the boars’ tail base. However, the development of the boars’ heels and claws was found to be significantly influenced by mechanical environmental factors and not associated with the piglets’ scores. These findings imply that heritable, endogenous processes, as proposed for SINS, also visibly impact the phenotype of the AI boar. This study’s fundamental premise suggests that pre-selecting AI boars could mitigate the occurrence of SINS and enhance piglet health and welfare.
Keywords: ddc:630